Measurements of the Bioclimatic Effects of Groups of Trees in an Argentinian Arid City - Kurban, Alejandra Silvia (2004)
The characteristics and distribution of groups of trees in an urban area as a contribution to the population's hygrothermic comfort were studied in the urban canyons of a city located on the arid zone of SouthAmerica (San Juan - Argentina). The paper studies the shade produced by the trees taking into account their actual conditions, since the urban specimens usually are modified, as compared with those in the natural environment. It tries to validate the international standards as a bioclimatic factor of great value in an arid zone. The values of the Shaded Area and Effective Arboreal Covering are analyzed for their real shade efficiency, considering the permeability to solar radiation in winter and summer, the overlapping of the tree tops and the general state of the trees. It shows that the average shade in the whole city represents 28.0% of the horizontal area of the urban canyon, or 10.0 m2 per inhababitant if related to the number of people, as an average for the whole city; both values diminish to 16% and 6.0 m2/inhab. respectively when the Effective Arboreal Covering is considered. It is concluded that in a city with a mesothermal arid climate, having on average a Land Occupation Factor about 50.0% and a Building Density about 35000m3/ha, the optimum shade area considering the bioclimatic requirements for summer, is between 70.0% and 75.0% of the total horizontal area of the urban canyons. These values are compared, with international standards, and it is shown that these standards do not consider a number of factors, such as permeability to solar radiation, seasonal effects, and the orientation of streets and buildings with respect to sunlight.